2018
DOI: 10.1111/sji.12736
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cytokines secreted by CD4+CD25highCD127low regulatory T cells inhibits ovarian cancer progression

Abstract: Epithelial ovarian cancer (EOC) is one of the major malignant cancers with high rates of early metastasis in which regulatory T cells (Tregs) play an important role. Tregs suppress immune responses and promote the development of tumours in patients with EOC. However, the underlying mechanisms remain unclear. In this study, we found higher levels of CD4+CD25highCD127low Tregs in patients with EOC than in patients with benign ovarian tumours and healthy donors. The immune inhibitory effect of Tregs functions by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Furthermore, they can also be detected in the tumor microenvironment (TME). In various cancer entities, a high number of Treg has been reported to be associated with a worse prognosis by suppressing antitumor responses [32][33][34] in, for example epithelial ovarian cancer [35,36] and non-small-cell lung cancer [37]. It is well known, that the Treg marker FoxP3 can be upregulated or downregulated depending on the human cancer type [26,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they can also be detected in the tumor microenvironment (TME). In various cancer entities, a high number of Treg has been reported to be associated with a worse prognosis by suppressing antitumor responses [32][33][34] in, for example epithelial ovarian cancer [35,36] and non-small-cell lung cancer [37]. It is well known, that the Treg marker FoxP3 can be upregulated or downregulated depending on the human cancer type [26,38].…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation rate of Treg seemed to be even more increased when the tumor cells expressed Human Leucocyte Antigen G [ 47 ] or by transforming growth factor-ß1 [ 48 ]. In summary, these data indicate that induced Treg are immunosuppressive and promote tumor progression [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 92 ] Beyond OC cells, IL-10 has been found in several human carcinoma cell lines and cells isolated directly from tumor tissues, with pancreatic cancer cell-derived IL-10 suppressing CTL lytic function of T cells [ 93 95 ]. The metastatic ability of EOC cells correlates with IL-10 and TGF-β in ascites, associated with altered MMP-2 and TIMP-2 levels [ 96 ] (Fig. 1 ).…”
Section: Il-10-producing Cells and The Possible Functionsmentioning
confidence: 99%
“…CD24 might be a potential target as well, but data are outstanding [7]. The correlation of EOC cell metastasis with the levels of TGF-β1 or IL-10 suggested that immunosuppressive cytokines could be a novel target for inhibiting EOC progression [81].…”
Section: Promising New Approaches With Possible Future Relevancementioning
confidence: 99%